Pengaruh intervensi pendidikan gizi terhadap peningkatan pengetahuan gizi, perubahan asupan zat gizi dan indeks massa tubuh remaja kelebihan berat badan - Nurmasyita, Nurmasyita; Widjanarko, Bagoes; Margawati, Ani (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2015)
Background: Adolescence overweight due to excessive intake and physical inactivity. This situation will continue until adulthood and cause degenerative diseases.  The prevalence of overweight adolescents  in senior high school Pontianak is 16,8% (higher than prevalence of obese adolescents in Indonesia).Objective: Analyze impact of nutrition education intervention to increase nutritional knowledge, change nutrient intake and Body Mass Index (BMI) among adolescent overweight in Pontianak high school.Methods: Quasi-experimental study design with control group pre-post test design. Nutrition education intervention to treatment group was gave once a week for 3 months and control group was gave only one for 3 months study. The subject are 73 overweight high school students, taken by purposive sampling and divided into 2 groups: 36 treatment group and 37 control group. Statistical analysis using paired t-test, Wilcoxon test, Independent t-test, Mann-Whitney Test and covariance.Results: This result shows that nutrition education intervention increase nutrition knowledge score (9.58±11.82) and fiber intake (1.05±5.29 g) in treatment group; reduce energy sufficiency rate in treatment and control group (12.42±16.77% and 10.18±0.54%); reduce protein adequacy rate (7.61±12.05%%), carbohydrate intake (3.78±6.71%) and reduce fat intake (3.11±3.96%) in treatment group; reduce BMI in treatment and control group (0.58±0.67 kg/m2 and 0.12±0.34 kg/m2).Conclusion: Nutrition education in overweight adolescent can decrease BMI among them through increase their nutrition knowledge. Nutrition knowledge of overweight adolescent decrease energy adequacy level, protein adequacy level, carbohydrate intake percentage, fat intake percentage, and increase fiber intake.